The influence of domestic and international interest rates on the ISEQ - Bredin, Don; Gavin, Caroline; O'Reilly, Gerard (Economic & Social Studies, 2003)
We investigate the influence of international and domestic monetary policy shocks on the Irish stock market. Specifically, we analyse the impact of (un)expected changes in domestic, US, UK and German/euro area policy rates on the ISEQ between 1988 to 2002 in an event type study. Our decomposition of (un)expected changes in policy rates are based on futures markets and is akin to Kuttner (2001). In the absence of an Irish interest rate futures market, we use a more indirect method by appealing to the expectations theory of the term structure of interest rates. Overall, our results suggest that, with the exception of the US, unanticipated changes in domestic and international interest rates appear to have little significant influence on the Irish stock market.
Paper presented at the Seventeenth Annual Conference of the Irish Economic Association, Limerick, 2003
Keywords: Interest rates; Monetary policy; Stock market; Ireland